Penerapan Pendekatan Deep Learning dalam Pembelajaran Matematika Materi Teorema Phytagoras untuk Meningkatkan Hasil Belajar Siswa - Helviani, Helviani; Rismawati, Rismawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to see the improvement of mathematics learning outcomes of eight grade students of Ibnu Sina Junior High School on the Pythagorean theorem material through the application of a deep learning approach. The method used is quantitative with a quasi-experimental design and nonequivalent control group design. All 24 seventh grade students were involved as a saturated research population, which was divided into an experimental class (VIIIA, n = 12) using a deep learning approach and a control class (VIIIB, n = 12) taught using conventional methods. Data collection was carried out through a learning outcome test in the form of descriptive questions given before (pretest) and after treatment (post-test). The data obtained were then analyzed using descriptive and inferential statistics with the help of SPSS version 27. The results of the descriptive statistical analysis indicated that the mean post-test score of the experimental group reached 84.17 while the control group was 67.92. Through hypothesis testing, a significance value of 0.000 < 0.05 was obtained, meaning is rejected and is accepted. The conclusion is that the application of the deep learning approach is significantly effective in improving mathematics learning outcomes in junior high schools Keyword: Mathematics, Pythagorean Theorem, Deep Learning Approach, Learning Outcomes